21-Gene Recurrence Score Assay Could Not Predict Benefit of Post-mastectomy Radiotherapy in T1-2 N1mic ER-Positive HER2-Negative Breast Cancer - Zhang, Wen-Wen; Tong, Qin; Sun, Jia-Yuan; Hua, Xin; Long, Zhi-Qing; Deng, Jia-Peng; Dong, Yong; Li, Feng-Yan; He, Zhen-Yu; Wu, San-Gang; Lin, Huan-Xin (Frontiers in Oncology, 2019)
Introduction: It is still controversial whether post-mastectomy radiotherapy (PMRT) is necessary for women with T1-2 N1mic ER-positive HER2-negative breast cancer. The 21-gene recurrence score (RS) assay has been validated in T1-2 N1 breast cancer to be prognostic of locoregional recurrence (LRR) and overall survival (OS). This study is aimed to evaluate the predict value of 21-gene recurrence score assay for the benefit of PMRT in T1-2 N1mic ER-positive HER2-negative breast cancer. Methods: A population-based cohort study was performed on women with T1-2 N1mic ER-positive HER2-negative breast cancer who underwent mastectomy and were evaluated using the 21-gene RS in the Surveillance, Epidemiology, and End Results (SEER) registry between 2004 and 2015. Clinical characteristics as well as OS and breast cancer-specific survival (BCSS) were compared between patients with and without PMRT in patients with a Low-, Intermediate-, and High-RS. Multivariate COX regression analysis was performed to investigate if the 21-gene RS assay could predict benefit of PMRT in this group of breast cancer patients. Results: A total of 1571 patients met the criteria of our study and were enrolled, including 970 patients in the Low-Risk group (score <18), 508 in the Intermediate-Risk group (score 18-30), and 93 patients in the High-Risk group (score >30). In the High-Risk group, there were more patients with age ≥50 (87.0% vs. 64.3%, P = 0.040) and received chemotherapy with a borderline significance (91.3% vs. 72.9%, P = 0.066) in the PMRT subgroup than in the no PMRT subgroup. In all three groups, OS was comparable between the PMRT subgroup and the no PMRT subgroup. Furthermore, multivariate analysis showed no predict the value of the 21-gene RS assay for PMRT in any of the three risk groups in terms of OS. Conclusion: This study showed that the 21-gene RS assay was not able to predict benefit of PMRT for OS in women with T1-2 N1mic ER-positive HER2-negative breast cancer. However, further prospective larger sample-size trials are warranted.